A comparison of teaching opportunities for rural and urban family medicine residents. Issue 2 (10th December 2019) - Jattan, Aaron; Penner, Charles G.; Giesbrecht, Marsha; Malin, Greg; Au, Lillian L.; Archibald, Douglas; François, José; Dufour, Karlyne; Kim, George P.
Abstract: Context: Medical schools of geographically large nations have expanded into rural areas to facilitate the development of a sustainable rural pipeline of physicians. Preceptor, or clinical teacher, recruitment at these sites has been an ongoing challenge. However, residents‐as‐teachers (RaT) curricula have not been modified to support the development of rural teachers. This study aimed to compare teaching opportunities between rural and urban family medicine residents and to identify mechanisms underlying potential differences. Methods: Year‐1 and Year‐2 family medicine residents at seven Canadian institutions participated in a mixed‐methods study utilising a quantitative survey and a qualitative interview. Rural and urban residents rated the quantity and types of teaching opportunities available during their training, from which a chi‐squared analysis was completed. Volunteer respondents participated in a structured interview, from which a thematic analysis was performed. Results: Rural family medicine residents had fewer opportunities to teach compared to their urban colleagues. This discrepancy was seen across multiple domains, including informal opportunities when on family medicine rotations, χ 2 (4, n = 242) = 45.26, P < .000, Bonferroni's adjusted P < .000. Thematic analysis centred around determining factors influencing teaching opportunities and identified that the academic context, personal factors and programme factors were key dimensions. Within these dimensions, the number of medical students, a desire to be an educator and administrative support were cited as influences on teaching opportunities. Conclusions: The lack of teaching opportunities for rural trainees is attributable to a combination of practical and organisational factors revealed through thematic analysis. If rural graduates are not comfortable balancing the demands of service and teaching, this could compound the already prevalent issue of rural preceptor recruitment. It is essential to develop a rural‐focused RaT curriculum to close this gap and produce competent educators who are ready to inspire generations of rural physicians. Abstract : As arguments mount for increasing the amount of training in rural family medicine environments, requiring the need for educational expertise in those contexts, our field may have overlooked how hard it is for trainees to develop rural environment‐focused teaching skills.